Minimizing Mitogenic Potency of Insulin Analogues Through Modification of a Disulfide Bond - Ong, Shee Chee; Belgi, Alessia; Merriman, Allanah L.; Delaine, Carlie A.; van Lierop, Bianca; Andrikopoulos, Sofianos; Robinson, Andrea J.; Forbes, Briony E. (Frontiers in Endocrinology, 2022)
The mechanisms by which insulin activates the insulin receptor to promote metabolic processes and cellular growth are still not clear. Significant advances have been gained from recent structural studies in understanding how insulin binds to its receptor. However, the way in which specific interactions lead to either metabolic or mitogenic signalling remains unknown. Currently there are only a few examples of insulin receptor agonists that have biased signalling properties. Here we use novel insulin analogues that differ only in the chemical composition at the A6–A11 bond, as it has been changed to a rigid, non-reducible C=C linkage (dicarba bond), to reveal mechanisms underlying signaling bias. We show that introduction of an A6-A11 cis-dicarba bond into either native insulin or the basal/long acting insulin glargine results in biased signalling analogues with low mitogenic potency. This can be attributed to reduced insulin receptor activation that prevents effective receptor internalization and mitogenic signalling. Insight gained into the receptor interactions affected by insertion of an A6-A11 cis-dicarba bond will ultimately assist in the development of new insulin analogues for the treatment of diabetes that confer low mitogenic activity and therefore pose minimal risk of promoting cancer with long term use.